Why Use Board Games in Leisure-Time Centres? Prominent Staff Discourses and Described Subject Positions When Playing with Children - Haglund, Björn; Peterson, Louise (INTERNATIONAL JOURNAL FOR RESEARCH ON EXTENDED EDUCATION, 2017)
Board games are traditionally seen as an important Swedish leisure-time centre activity, but research regarding this activity is sparse. This study aims to fill part of that void through a web survey directed to members in a closed Facebook group focusing on leisure-time centres. Fifty-five informants' answers were analysed using critical discourse analysis to find why staff at leisure-time centres use board games. The article also discusses the subject positions the staff use when playing board games with the children. The results reveal four prominent discourses, which were termed: supporting social structure, learning social competence, substituting digital games, and learning cognitive abilities. The results also reveal three subject positions while playing board games: developer, supervising judge, and participant. The informants' discourses regarding their reasons for using board games and the positions the staff settled into while playing board games drew mostly from a social pedagogical arena. However, features that emphasize traditional school related content are also evident.